The Effect of Red Dragon Fruit (Hylocereus polyrhizus) on ROS Plasma of Overweight Sprague Dawley Rats - Solehah, Novia Zuriatun; Prayitno, Adi; Pamungkasari, Eti Poncorini (Media Gizi Indonesia, 2022)
Red dragon fruit (Hylocereus polyrhizus) contains antioxidants, namely vitamin C, flavonoids, phenols, and betacyanins that can reduce or inhibit oxidative stress in the body. Excess body weight condition is associated with an increase in oxidative stress due to a decrease in antioxidants. This study was aimed to analyze the effects of red dragon fruit on the level of ROS (MDA) of overweight Sprague-Dawley rats. It used experimental analysis by using pre- and-posttest design with control group. A total sample of 30 male white Sprague-Dawley rats aged 8-12 weeks old with 150-200g of body weight were divided into 6 groups, namely: normal, negative control (KN), positive control (KP), red dragon fruit juice 3.5 g/200gBW (P1), overweight + dragon fruit juice 7 g/200gBW (P2), overweight + dragon fruit juice 10.5g/200gBW (P3) and were observed for 14 days. ROS levels were measured in the beginning and at the end of the intervention by using MDA markers with TBARs method. The results of MDA level measurements were 3.83 ± 0.13 in the KP group, 7.18 ± 0.27 in the P1 group, 5.30 ± 0.30 in the P2 group, and 4.35 ± 0.42 in the P3 group. The results of one-way ANOVA test showed a significant difference in MDA levels in all intervention groups compared to those of the normal and KN groups (p = 0.05). In conclusion, red dragon fruit intake can reduce ROS levels in overweight Sprague-Dawley rats.